Cropping systems sustainability: Inoculation and fertilisation effect on sulla performances in a new cultivation area - Sulas, Leonardo; Piluzza, Giovanna; Salis, Mauro; Deligios, Paola A.; Ledda, Luigi; Canu, Simone (Italian Journal of Agronomy, 2017)
To assess the feasibility of the sulla [Sulla coronaria (L.) Medik] forage legume in a new agroecosystem, its host-specific symbiotic interaction needs to be taken into account. This study aimed to investigate the effects of inoculation and nitrogen (N) fertiliser on productive performances and N-fixation ability of sulla established in a new habitat within a Mediterranean agropastoral area. Sulla plants, previously inoculated (with peat-based, liquid inoculants, and using soil from an existing sulla field) and unfertilised or N fertilised were evaluated in Sardinia (Italy). During 2013-2014, sulla plants were sampled at four growing stages, from vegetative stage to seed set, and shoot length, shoot dry matter (DM) yield and N content were monitored. Moreover, atom% 15N isotopic excess, proportion of N derived from the atmosphere and fixed N of sulla shoots were quantified. Inoculation and N fertilisation both affected growth, DM and N yields, and N-fixation of sulla. Compared to the best inoculated treatment, the DM yield and fixed N of the control only represented 10 to 22% and 2 to 11%, respectively. Nitrogen fertilisation caused temporary decreases in the N fixing ability of sulla. Results pointed out that rhizobial inoculation is essential for the exploitation of sulla outside its traditional cropping area.